The role of climate, vegetation, and soil factors on carbon fluxes in Chinese drylands - Liu, Zhaogang; Chen, Zhi; Yu, Guirui; Zhang, Weikang; Zhang, Tianyou; Han, Lang (Frontiers in Plant Science, 2023)
Global change is affecting terrestrial carbon (C) fluxes. The effect of climate on ecosystem C fluxes (Gross primary productivity (GPP), ecosystem respiration (ER), and net ecosystem productivity (NEP)) in drylands has been largely explored, but the roles of other concurrently changing factors, such as vegetation condition and nutrient availability, remain elusive. We used eddy-covariance C-flux measurements from 45 ecosystems with concurrent information on climate (mean annual temperature (MAT) and mean annual precipitation (MAP)), soil (soil moisture (SM) and soil total nitrogen content (soil N)), and vegetation (leaf area index (LAI) and leaf nitrogen content (LNC)) factors, to assess their roles on C fluxes. The results showed that drylands in China were weak C sinks. GPP and ER were positively correlated with MAP, while they were negatively correlated with MAT. NEP showed first decreased and then increased with increasing MAT and MAP, and 6.6 ℃ and 207 mm were the boundary for NEP response to MAT and MAP. SM, soil N, LAI, and MAP were the main factors affecting GPP and ER. However, SM and LNC had the most important influence on NEP. Compare to climate and vegetation factors, soil factors (SM and soil N) had a greater impact on C fluxes in drylands. Climate factors mainly affected C fluxes by regulating vegetation and soil factors. To accurately estimate the global C balance and predict the response of ecosystems to environmental change, it is necessary to fully consider the discrepant effects of climate, soil, and vegetation factors on C fluxes, as well as the cascade relationship between different factors.